„KIEDY MYŚLĘ: OJCZYZNA, SZUKAM DROGI”. TEO-LOGICZNA PERSPEKTYWA JANA PAWŁA II W 100-LECIE NIEPODLEGŁOŚCI POLSKI - Szymik, Jerzy (Studia Pastoralne, 2023)
Project titled ‘Polonia Restituta. The Decalogue for Poland on the 100th Anniversary of Independence’ is intended by its authors – the Ministry of Science and Higher Education and the Council for Social Affairs of the Polish Episcopal Conference – as a thought about the future of our Homeland and State, about ‘how Poland should look like’. It should be a thought from a clearly defined perspective of Catholic social science, that is a theo-logic perspective. The Minister explains: we need ‘an in-depth reflection on where we are going to and what for, what values should accompany our collective life, what values we should use as the basis to restructure our state’. And later: since ‘the role of the Catholic church is unique and incomparable with any other institution in our history’, consequently, ‘here and now, we will examine Poland through the prism of its teaching, which directed the generations of our ancestors.’ ‘Thinking Homeland … Civic virtues and patriotism on the 100th anniversary of regaining independence by Poland’ is one of the ‘commandments’ of the ‘Decalogue for Poland’ under elaboration, i.e. one out of ten segments of theo-logic thinking (the thought guided by the logics of social science derived from the science of God) and understanding of the phenomenon of Poland itself. The sub-title clearly specifies further that the subject of the said thought shall be a conjunction of civic virtues (= a set of attitudes resulting from the bonds joining a person and a state) and patriotism (= according to John Paul II: ‘love for everything relating to homeland’, a moral virtue of love to Homeland). And the questions like: how do they relate to each other, whether they are directly or inversely proportional to each other, what ethical/social spaces do they share and which ones are separate for them? etc. Whereas, the two-word title (being the title of Karol Wojtyła’s poem) enables, and – what is more: suggests, inclines – to provide the thought in the light of teaching of our great fellow citizen and compatriot, the saint Pope. Thus: what John Paul II tries to tell us about what is patriotic and what is civic and about the interrelationship, threats and perspectives between these two aspects? And what – this is the most important question – from his theo-logic thought in this subject could become ‘deca-logic’ (in the perspective of liability and morality) for Poland, for its conversion, good and future? Karol Wojtyła/John Paul II does not differentiate clearly (he does not formulate strict definitions, does not make differences) between patriotism and civic virtues. The fundamental string of his thought and teaching in this respect is directed towards in-depth understanding and description of patriotism, which leads to civic ethos (the so-called civic virtues, arete politike, that is, a set of attitudes which show concern about the common good, namely, the state). He presents these in several genealogical layers of his works and teaching: within the poetic layer (here, in particular, in his poem titled Thinking Homeland… of 1974), within the essayistic layer (here, in particular, in Memory and Identity, written in 1993 and 2005) and within the preacher’s and lecturer’s layer (here, for instance, in homilies and speeches made during pilgrimages to Poland, but not only in these cases, also in some speeches concerning the issue in question, among others, during his famous speech in the Paris-based seat of UNESCO in 1980). The poem Thinking Homeland…, a text exceptionally dense in terms of language and content, published five years after its creation, already during the pontificate, under a nick name, contains several splendid and well-known phrases of Wojtyła: ‘When I think: Homeland, then I express myself and put down my roots’; ‘Is it possible for history to flow against the current of consciences?’’ ‘the liturgy of history’. Fragments of Memory and Identity constitute its essayistic development and interpretation. It is in this work where John Paul II explains fundamental content of his theology of patriotism/civic virtues, homeland and nation, their history and culture. In short: Homeland is a heritage, a resource of goods (strictly interrelated spiritual and material values, culture and land) received ‘after ancestors’. The teaching of Christ includes the most in-depth elements of theological vision of the homeland – it ‘opens the notion of homeland towards eschatology and eternity, but by no means deprives it of its earthly content (!). Patriotism means the ‘love for homeland’, an internal attitude (pietas) and a moral virtue, falling within the scope of the 4th commandment of the Decalogue. Both homeland and nation have got their own theological roots and existential reference to the mystery of creation and – similarly as in case of a family – they constitute ‘natural communities’ (nature of a man is of social character; a nation ‘is not a fruit of an ordinary agreement’) and ‘remain realities that cannot be replaced’ (!). What is more to say and describe in more detail in this subject: ‘You cannot […] replace a nation with a state’, ‘the more you cannot convert the nation into the so-called democratic society’. The Pope reaches for Christology also in this case: ‘The mystery of personification, the foundation of the Church, belongs to the theology of nation’ and gives it proper justification and inalienability, direction and depth. Theology and theo-logics of homeland and nation, as well as a theological reflection over relationships between ‘man – nation– homeland – state – civic virtues’, protects the whole difficult, complicated conglomeration, exposed to vagueness and distortions against mistakes and their existential consequences (sometimes with terrible results), such as, on the one side eradication and orphanage, and on the other side, a nationalism (‘so as the inalienable function of the nation will not degenerate into nationalism’). Calling for the ‘”Jagiellonian” dimension of Polish identity’, the Pope writes that ‘Polish identity is, in fact, a multiplicity and pluralism, not parochialism and confinement’. At the same time, he defends the – nowadays attacked – strive for protection and development of the ‘nation’s identity’ against its dispersion in transnational and cosmopolitan structures. He does so through the category of culture, crediting it with fundamental significance in his theological thought concerning the nation and state (thus, also the patriotism and civic virtues). During his speech in the seat of UNESCO, he mentioned: ‘The nation is such a great community of people who are joined together with various bonds, but, above all, with culture. The nation exists ‘because of its culture’ and ‘for its culture’. […] There is a basic sovereignty of the society, expressed in the culture of nation. Simultaneously, it is the sovereignty through which a man becomes parallelly the most sovereign.’ He said a terrific thing about his experience of papal service: ‘with my experience of the history of my homeland, with my increasing experience of the value of nation, I was not a stranger for the people I met. On the contrary, my experience of homeland facilitated, to great extent, my contacts with people and nations on all the continents.’ Consequently, the basic conclusion from ‘thinking: Homeland’: when, in the Christian, ecclesiastically moderated space, ‘I express myself and put down my roots’ into what is native and national, then the process (and attitudes co-creating it) serves what is universal for all humans, transnational, universal, eternal. Strengthening of (arousing, developing and cleansing) patriotism constitutes the best way to strengthening of (arousing, developing and cleansing) virtues and civic attitudes. Let us emphasise it: both require protection – patriotism need protection against demons of nationalisms, civic virtues – against emptiness of a liberal state, where the nomo-, bureau-, and technocracy cannot defend the panegoism and atrophy of virtues. ‘When I think: Homeland, I’m looking for the way’ – wrote Wojtyła forty-four years ago. The way runs through the Baptism of Poland, teaches. The one dating back to more than a thousand years and the one, in which all subsequent generations should cleanse themselves. The Baptism will save Independent Poland and its citizens, it will bring the future to both the Homeland and State. The Baptism will put down its and their roots in the redemptive God’s mysteries of creation, personification and love.